The Importance of the Values Promoted by the Values Program at CIEX - Lazgare, Yohaly (CIEX JOURNAL, 2024)
Understanding and applying values in everyday life is essential for personal growth and societal harmony. Values serve as guiding principles, helping individuals navigate various situations and make ethical decisions. In this context, Kelum et al. (2021) define values as fundamental beliefs endorsed by society over time. These beliefs not only shape individual behavior but also contribute to the broader cultural fabric of society. However, understanding values goes beyond mere recognition; it requires practical application. As a student, reflecting on personal values and their implications in different scenarios is crucial for effective communication and interaction. Programs like CIEX offer platforms for such reflection, integrating discussions on values into education. By exploring values within the context of language learning, students gain insights into cultural nuances and develop communication skills aligned with societal norms. Thus, the intersection of values, education, and language fosters holistic personal and cultural development.